Self-expansion of entrepreneurial women in the family interface - Fickler, Michel (Człowiek i Społeczeństwo, 2025)
Purpose: This study addresses the experiences of entrepreneurial women within the family interface, examining how gender roles influence their professional identity as self-expansion. It aims to deepen understanding of their marital challenges and propose insights to advance their professional and marital success. Design/methodology/approach: The study is based on in-depth interviews with 38 middle-class women entrepreneurs (aged 35–36) managing business in Israel for over four years. data analysis follows a constructivist-qualitative approach. Findings: three key themes emerged: (1) negotiations on norms and role identity – conflict between family roles and self-expansion creates personal and marital tension, sometimes leading to divorce; (2) reduction or elimination of roles – some women forgo marriage or parenthood to achieve self-expansion; (3) reversal or change of roles – an egalitarian or reversed division of roles fosters self-expansion and family enrichment. Research limitations: This qualitative study relies on life stories, providing insights but challenging the process of recruitment and objectivity. Implications: It is recommended to develop educational programs for the empowerment of the self-expansion and marital support for the change of traditional roles alongside the extension of the cultural discussion on self-expansion.